Lynch syndrome screening in colorectal and endometrial cancers in Iceland - Katla R. Kluvers; Thordur Tryggvason; Vigdis Stefansdottir; Jon G. Jonasson; Petur Snaebjornsson; Sigurdis Haraldsdottir (Acta Oncologica, 2025)
Background and purpose: Screening for Lynch syndrome (LS) with mismatch repair (MMR) protein immunohistochemistry (IHC) in all patients with newly diagnosed colorectal (CRC) and endometrial cancer (EC) was implemented in Iceland in 2017. The aim of the study is to assess the accuracy of screening in 2020–2022 and compare it to 2017–2019 when screening was initiated. Patients/materials and methods: All patients diagnosed with CRC and EC according to the Icelandic Cancer Registry in 2020–2022 were included. Screening results were crossmatched with a genotyping database from deCODE to calculate sensitivity and specificity for LS detection. Results: In 2020–2022, 429 of 522 (82%) diagnosed CRCs were stained and 90 of 106 (85%) ECs, compared to 74% of CRCs and 82% of ECs in 2017–2019. The screening protocol was followed in 90% of cases for CRCs and 95% of cases for ECs compared to 89% and 68% during 2017–2019. The sensitivity of IHC as a screening method for LS was 70% and specificity 88% with a positive and negative predictive value of 8.4% and 99.4%, respectively. Interpretation: Three LS cases were missed with MMR IHC (1 MSH6 and 2 PMS2 carriers), it is possible these patients had sporadic cancers unrelated to their LS carrier status. MSH6 and PMS2 deficiency strongly predicts LS in Iceland.